Characteristics of participants who withdraw from surgical simulation-based educational research. (14th March 2018) - Vega Vega, Camila; Gostlow, Hannah Claire; Marlow, Nicholas; Babidge, Wendy; Maddern, Guy
Abstract : Introduction: The problems associated with recruitment and retention of patients in clinical trials have been widely addressed in literature; however, similar problems associated with healthcare workers are rarely reported. The aim of this paper is to outline the factors that can impede a participant's successful participation in a research project and to analyse the characteristics of participants that withdrew. Methods: The Laparoscopic Simulation Skills Program (LSSP) was a prospective randomised cohort study investigating the efficacy of self-directed learning for basic laparoscopic skills acquisition. Two hundred and seven medical students, junior doctors, as well as surgical and gynaecology trainees were enrolled between June 2015 and November 2016. Results: Fifty-six (27%) participants failed to attend the final assessment. Of these, 43 participants (77%) responded to the follow-up survey and/or phone contact regarding non-attendance. Most participants failed to attend due to lack of free time/conflicting clinical duties and university requirements. Participants who did not attend the final assessment and did not provide further responses were less motivated by a career in surgery, surgical simulation and perceived less benefits of laparoscopic simulation. The 43 participants who answered the survey and/or phone contact provided similar responses to the participants who completed the study requirements and had more intrinsic motivators to enrol. Conclusions: Clinical duties and other educational commitments are the biggest barriers to participation in simulation based-education research.